2019
DOI: 10.11118/actaun201967010075
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Digestate on Physical Properties of Soil in ZD Budišov

Abstract: One of the main objectives of crop establishment is adjustment of physical properties of soil, on which indicators of soil fertility as well as economic appreciation of the resulting yield depend. During 2014–2016 yield of corn and sorghum was observed in semi‑operational experiments of ZD Budišov in relation to the quantity of the applied digestate and simultaneously, the following physical properties of soil were analysed: porosity, compaction and soil structure. After the application of digestate the porosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Chatterjee and Mazumder brought attention to the possibility of structural degradation due to the often-high levels of sodium in digestate [65]. Jasa et al showed similar views on the topic, with digestate having more positive effects on sandy soils, while on heavy soils, it can be detrimental with respect to porosity and minimal air capacity, which can negatively affect plant fitness [66]. In our experiment, a divided dose of digestate (D4) showed a tendency to lower DON and T-2 levels in comparison to the application of the same amount (80 m 3 /kg) in one dose (D2).…”
Section: Discussionmentioning
confidence: 99%
“…Chatterjee and Mazumder brought attention to the possibility of structural degradation due to the often-high levels of sodium in digestate [65]. Jasa et al showed similar views on the topic, with digestate having more positive effects on sandy soils, while on heavy soils, it can be detrimental with respect to porosity and minimal air capacity, which can negatively affect plant fitness [66]. In our experiment, a divided dose of digestate (D4) showed a tendency to lower DON and T-2 levels in comparison to the application of the same amount (80 m 3 /kg) in one dose (D2).…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in southwestern Germany, it was found that digestate could be an adequate substitute for mineral fertilizer in sweet sorghum production [52]. The same reaction of sorghum plants to biosolids application was noted by Sigurnjak et al [53] in a study carried out in the Czech Republic under similar weather conditions. Digestate can be considered a synthetic N substitute without crop yield losses [54].…”
Section: Biomass Yieldmentioning
confidence: 52%
“…(1) no-tillage (NT), where weeds were mechanically removed and left upon the soil surface as a residue mulch; (2) conventional tillage (TILL) consisting of an inter-row harrowing (~20 cm) followed by a slight rolling; and (3) conventional tillage coupled with soil incorporation of the solid fraction of anaerobic digestate (DIG) at a rate of 30 Mg ha −1 , a dose close to that usually employed in agriculture and to that suggested by Caracciolo, et al [29] and Fernández-Bayo, et al [30] in their field trials testing C and N mineralization (Figure 1). The digestate was supplied during the 2016 growing season at the beginning of the trial (May 2016), while plant responses to the treatments were monitored over the following season in order to evaluate the mid-term effects on plant physiology in accordance with what was reported by Knoop, et al [31] and Jaša, et al [32]. Chemical fertilizers were applied only during the 2016 growing season (in early spring) before the start of the trial.…”
Section: Experimental Design and Soil Managementmentioning
confidence: 99%